Multiscale Photo-Based In-Situ and Operando Spectroscopies in Time and Energy Landscapes. Issue 2 (4th March 2017) - Velasco-Velez, Juan-Jesus; Hävecker, Michael; Knop-Gericke, Axel; Schwanke, Christoph; Xi, Lifei; Lange, Kathrin M.; Xiao, Jie; Tesch, Marc F.; Golnak, Ronny; Petit, Tristan; Puskar, Ljiljana; Schade, Ulrich; et al.
Abstract : Following catalytic reactions, in-situ and operando are now the focus of a number of dedicated experiments at light sources which have been developed to track the electronic and molecular structural dynamics of catalysts. The challenges for this goal are two-fold: first, the development of spectroscopic tools in the energy domain and time domain is required. The photocatalytic processes have early dynamics of tens of femtoseconds, while further reaction takes seconds, minutes, and even hours. Second, a combination of tools to probe processes not only in solids, but also in solutions and at interfaces, is now needed. In this special issue, we present recent developments at the synchrotron facility BESSY II using photon energy from the infrared and extreme ultraviolet up to the soft X-ray regime for in-situ and operando applications addressing these two major challenges. As this work is a result of contributions from several groups, each section will present the group's activities and related team members involved.